Pengaruh Faktor Psikologis, Sosial, dan Teknis dalam Meningkatkan Kepatuhan UMKM pada Pelaporan Pajak Berbasis Digital - Agustria, Deni; Juita, Verni (Universitas Negeri Padang, 2025)
This study explores how psychological factors (tax morale, trust, and awareness), social factors (social environment), and technical factors (ease of use and convenience) influence tax reporting compliance among micro, small, and medium enterprises (MSMEs) utilizing digital platforms. Using a multiple linear regression approach, data were collected from 239 MSME taxpayers across Indonesia through a non-probability sampling technique, specifically convenience sampling. The analysis revealed that tax morale, awareness, and perceived convenience do not significantly impact digital tax reporting compliance. In contrast, trust and social environment emerged as significant predictors of compliance behavior. These findings highlight the critical role of trust in the system and social influence in shaping tax behavior, suggesting that efforts to enhance compliance among MSMEs should go beyond improving system usability and also focus on building trust and supportive social norms within the digital taxation ecosystem.